Motivating Students to Learn English Speaking through Collaborative Activities - Asmi Rusmanayanti; Sirajuddin Kamal; Elsa Rosalina (TLEMC (Teaching and Learning English in Multicultural Contexts), 2021)
Motivation plays an indispensable role in the students' English language learning. As a result, teachers are expected to be able to employ miscellaneous teaching activities to enhance the students' motivation. One of them is collaborative teaching activities. In particular, collaborative teaching activities should not only engage students to learn enthusiastically but also help teachers organize and prepare their teaching practices flexibly. The present study accentuated to delineate students’ motivation on the implementation of collaborative teaching activities during learning English speaking. The participants were ten students of a university in Banjarmasin, Indonesia. The data were gathered through administering an open-ended questionnaire and analyzed with Thematic Analysis (TA) (Braun Clarke, 2006). The findings reported that students were motivated to learn English speaking through collaborative activities.